Heat stress resistance in Camelina sativa: effects on morphology, physiology, yield, and seed quality - Alberghini, Barbara; Zanetti, Federica; Ferioli, Federico; Haslam, Richard P.; Silvestre, Susana; Monti, Andrea (Frontiers in Plant Science, 2025)
Cultivated crops are increasingly exposed to episodes of extreme heat. In the Mediterranean basin, crops often experience heat stress during spring or summer, coinciding with flowering and seed ripening. Recently, Camelina sativa has emerged as an alternative oilseed crop of interest due to its resistance to abiotic stresses. To investigate possible mechanisms underlying camelina’s ability to cope with heat stress and to evaluate the role of tocopherols, two spring varieties (Cypress and Omega) were tested in two controlled-environment experiments. Heat was imposed for five consecutive days either from the end of flowering (EXP1) or from the stage when siliques reached their final size (EXP2). Early imposition of heat stress (EXP1) had the greatest impact on camelina morphological parameters during the growth cycle. At harvest in EXP1, only the genotype significantly affected plant height and seed yield, with Omega producing taller plants and higher seed yield (0.83 g per plant) compared with Cypress (0.70 g per plant). In EXP2, cultivar significantly affected only straw weight, which was higher in Omega. Nonetheless, Cypress exhibited the highest 1,000-seed weight in both experiments (1.36 g in EXP1 and 1.34 g in EXP2). Seed oil content was reduced by heat stress (− 9.89% in EXP1 and − 11.6% in EXP2, respectively). Fatty acid composition in EXP1 was mainly influenced by the cultivar, except for C18:1, whereas in EXP2, heat stress predominantly affected 18-carbon fatty acids. Total tocopherol content was largely under genetic control, and although α-tocopherol is associated with responses to abiotic stress, it increased only when stress was imposed at a later stage (+ 75.8% in the stressed plants). Despite the high tocopherol content of camelina, it appeared to contribute to plant stress resistance only under late-stage heat stress dueing seed maturation.